A Flexible Multidomain Structure Drives the Function of the Urokinase-type Plasminogen Activator Receptor (uPAR) - Mertens, Haydyn D. T. (American Society for Biochemistry and Molecular Biology, 2012)
The urokinase-type plasminogen activator receptor (uPAR) provides a rendezvous between proteolytic degradation of the extracellular matrix and integrin-mediated adhesion to vitronectin. These processes are, however, tightly linked because the high affinity binding of urokinase regulates the binding of uPAR to matrix-embedded vitronectin. Although crystal structures exist to define the corresponding static bi- and trimolecular receptor complexes, it is evident that the dynamic property of uPAR plays a decisive role in its function. In the present study, we combine small angle x-ray scattering, hydrogen-deuterium exchange, and surface plasmon resonance to develop a structural model describing the allosteric regulation of uPAR. We show that the flexibility of its N-terminal domain provides the key for understanding this allosteric mechanism. Importantly, our model has direct implications for understanding uPAR-assisted cell adhesion and migration as well as for translational research, including targeted intervention therapy and non-invasive tumor imaging in vivo.